ChemInform Abstract: A Concise Total Synthesis of Breitfussin A and B. Issue 21 (May 2015) - Pandey, Sunil Kumar; Guttormsen, Yngve; Haug, Bengt Erik; Hedberg, Christian; Bayer, Annette
Abstract The first total synthesis of the title compounds [A (Ia) and B (Ib)] from phenol derivative is reported in 7.2% and 4.3% overall yields, respectively.